The Effect of Project Based Learning Approach on Computational Thinking Skills and Programming Self-Efficacy Beliefs - ERGİN, Hayrünnisa; ARIKAN, Yüksel Deniz (Academic Journal of Information Technology, 2023)
The aim of this study is to reveal the effect of project use on students' self-efficacy beliefs towards programming and their computational thinking skills. A one-group pretest-posttest experimental design was used in the study. The research was conducted in 2018 with 14 12th-grade students in a Vocational and Technical High School in Izmir. In the research, the application of project use in programming teaching lasted 18 weeks. The research data were collected with the Self-Efficacy Scale for Programming (SESP) developed by Altun and Mazman (2012) and the Computer Thinking Skill Levels Scale (CTSLS) developed by Korkmaz, Çakır, Özden, Oluk, Sarıoğlu (2015). Wilcoxon Signed Ranks Test, one of the nonparametric tests, was used to analyze the research data. As a result of the study, it was observed that the use of projects in programming instruction had a positive effect on students' self-efficacy in programming, while it did not have a significant effect on their computational thinking skills. Based on the results of the research, it is recommended to teach block-based programming before text-based programming, to include game-themed activities, to ensure active participation of students, and to use multidimensional and alternative measurement tools to measure computational thinking skills to comprehend algorithm stages in programming instruction.